2020
DOI: 10.1136/archdischild-2020-320214
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for the child public health response to the COVID-19 pandemic recovery in England

Abstract: Child health is at risk from the unintended consequences of the COVID-19 response and will suffer further unless it is given proper consideration. The pandemic can be conceived as a systemic shock to the wider determinants of child health, with impacts on family functioning and income, access to healthcare and education. This article outlines COVID-19 impacts on children in England. Key priorities relate to the diversion of healthcare during lockdown; interruption and return to schooling; increased health risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 21 publications
0
43
0
2
Order By: Relevance
“…By far the most devastating long term costs of the pandemic are likely to fall on today’s children as they grow, develop, and forge their own economic futures 25. Child poverty is already the biggest threat to child health and development in the UK and globally,10 so the predicted increase is concerning 11.…”
Section: Long Term Forecastmentioning
confidence: 99%
See 1 more Smart Citation
“…By far the most devastating long term costs of the pandemic are likely to fall on today’s children as they grow, develop, and forge their own economic futures 25. Child poverty is already the biggest threat to child health and development in the UK and globally,10 so the predicted increase is concerning 11.…”
Section: Long Term Forecastmentioning
confidence: 99%
“…Containment and lockdown measures have disproportionately affected low income families with young children 5. Recent research identified the extra costs involved in having children at home for longer without access to vital free services, requiring increased spending on food, heating, and occupying children indoors.…”
mentioning
confidence: 99%
“…It complements quantitative surveys (Dodd et al, 2020; Public Health Scotland, 2020) by providing in-depth understanding of the stresses parents and their children face. These findings will be important for improving the support provided to families during future restrictions and informing plans for longer-term recovery (Hefferon et al, 2020). We note however that we only include the perspectives of parents, rather than the children themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The course of SARS-CoV-2 infection is rarely severe in children and adolescents (8)(9)(10). However, the long-term consequences of the limited access to essential medical care resulting from the pandemic restrictions should not be underestimated (11)(12)(13)(14)(15)(16). Pediatric consultations in primary care and in hospitals dropped dramatically due to the fearfulness of parents and restrictions in the health care delivery (17).…”
Section: Essential Pediatric Carementioning
confidence: 99%